Analysis of Factors Affecting Yield of Agricultural Crops in Bahawalpur District: Analysis of Factors of Major Agricultural Crops - Muhammad Akbar Ali Shah; Mohsin, Muhammad; Chesneau, Christophe; Zulfiqar, Asma; Jamal, Farrukh; Nadeem, Kashif; Sherwani, Rehan Ahmed Khan (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The main objective of this paper is to analyze and investigate the factors/variables which are affecting the yield/acre of the major crops in the district of Bahawalpur. Secondary data of crops is obtained from the Crop Reporting Service (CRS), Agriculture Department, Government of the Punjab for the period 2008-2016. Multiple Linear Regression (MLRM) models are utilized to check the effects of 12 independent variables (regressors) on the production of major crops. The findings revealed that factors such as the plough and rotavator number, planking, irrigation, seed type, seed treatment, DAP and urea fertilizer, farmyard manure, latest varieties, certified seed, weed spray, diseases and pests' sprays are found to be contributing factors to a higher yield of all crops, whereas soil type (kalrathi), excessive seed rate, home seed, weeds, diseases, and pests' attack are found to be foes. Except for the factors (fresh and ratoon, seed type) sugarcane, (seed treatment, seed quantity; diseases attack), rice, and (other fertilizer and amount of watering) cotton, all the factors were found to be statistically significant. Descriptive analysis revealed that 60-70% of farmers used less and unbalanced quantities of inputs, which are the main cause of lower yield/acre of all crops in the study area.